Electrochemical Performance of \(\text{Na}_{0.44}\text{MnO}_{2}\) Synthesized by Hydrothermal Method Using as a Cathode Material for Sodium Ion Batteries - Ta, Tan Anh; Pham, Long Duy; Nguyen, Hieu Sy; Hoang, Chung Vu; Le, Chi Ha; Dang, Chien Tran; Nguyen, Hoa Thi Thu; Nguyen, Nghia Van (Communications in Physics, 2017)
Orthorhombic Na0.44MnO2 with an S-shape tunnel structure was successfully synthesized by a hydrothermal method. The Na0.44MnO2 material has lattice parameters of a = 9.0842 Å, b = 26.2889 Å, and c = 2.8245 Å. Scanning electron microscope analysis reveals that the morphologies of Na0.44MnO2 consist of Na0.44MnO2 nanowires with diameters of about 30-50 nm and Na0.44MnO2 particles with the size in the range of 200 to 500 nm. The first charge and discharge capacities of Na0.44MnO2 cathode, at 0.1 C between 2.0-4.0 V, are 66.2 mAh g-1 and 62.7 mAh g-1, respectively. The Na0.44MnO2 has an excellent cycle stability with 85.3% of capacity retention over 50 cycles. The coulombic efficiency of Na0.44MnO2 material is approximately 90% after 70 cycles. It is suggested that the structure of Na0.44MnO2 is stable during cycling and Na0.44MnO2 can be a promising cathode material for sodium ion batteries.